Analisis Penghindaran Pajak pada Pengaruh Mediasi Pengampunan Pajak terhadap Nilai Perusahaan Manufaktur di Bursa Efek Indonesia - Melanny Methasari; Gogi Kurniawan (Sekolah Tinggi Ilmu Ekonomi Yapan, 2022)
This study aims to examine the effect of tax amnesty on firm value with tax avoidance as a mediating variable in the financial statements of manufacturing companies listed on the Stock Exchange which disclose PSAK 70. Tax amnesty is proxied by a dummy variable, firm value is proxied by the ratio Q, and tax avoidance is proxied by cash effectiveness. tax ratios. This type of research is quantitative with a population of 173 companies. Determination of the sample using the purposive sampling method with the criteria of being listed on the IDX during the 2017-2021 period, obtaining tax underpayment status during the 2017-2021 period, and participating in the tax amnesty program. Research using the WarpPLS 7.0 tool, the results obtained that tax avoidance cannot be a mediating variable for the effect of tax amnesty on firm value